Design of expert system to determine a major in higher Education using forward chaining method - Herawan Hayadi, B.; Ema Wulansari, Rizky; Mouludi, Isra; Candra, Oriza; ., Syamsuarnis; Saputra, Rusli (International Journal of Engineering and Technology, 2018)
The problem of this study was how to design aidsto assist students to introduce their potential and ability that they have. So that, they could choose an exact major in higher education based on their potential and ability. This study aimed to design expert system software to determine a major in higher education based on Multiple Intelligence. Design of expert system software used UML (Unified Modelling Language) process and Microsoft Access as a data base.Â Â